Strategi Penguatan Modal Sosial Perempuan Tani dalam Pemanfaatan Lahan Pekarangan Terbatas di Kabupaten Bogor - Sulaiman, Ageng Hasanah; Wahyuni, Ekawati Sri; Adiwibowo, Soeryo (Jurnal Penyuluhan, 2019)
Home garden and people’s living area has a potential to be a source of family food. This paper aimed to describe and analyze the performance of the Kawasan Rumah Pangan Lestari (KRPL) Program. Based on the results, a strategy to strengthen the social capital of the women farmers in home garden utilization inBogor District was formulated. The survey method used to get an overview of the performance of the KRPL in the three KRPL groups. Case studies were used to explore social capital, the role of companion, and administration management in one KRPL group. KRPL’s performance showed that, nurseries and demonstration plots (demplot) were not managed properly, Rumah Pangan Lestari (RPL) were still managed independently by members, and administrative management is not yet orderly. Social capital, the role of companion, and administration management also determine the performance of the KRPL. An action program to avoid future KRPL failures has been prepared.